A Facile Synthesis and Chemoselective Reactions of Dihydrothiouracils - Kumar, Varun; Khatik, Gopal L.; Pal, Anang; Praneeth, Mohan R.; Bhattarai, Sanjay; Nair, Vipin A. (Synlett, 2012)
A highly efficient procedure was devised for the synthesis of 3-(3-arylthioureido)propanoic/butanoic acid and its cyclization to (3-aryl/3-aryl-6-methyl)-2-thioxotetrahydropyrimidin-4(1H)-one derivatives. Carbonyl diimidazole proved to be a very effective coupling reagent for the cyclization. Studies carried out to examine the ambident nature of the thioamide moiety towards substitution reactions demonstrated the preference for alkylation at sulfur, and acylation and 1,4-addition at nitrogen.
Keywords: uracils; amino esters; carbonyl diimidazole; thioamide; ambident nucleophile